PENGARUH TINGKAT PENDIDIKAN TERHADAP PRESTASI KERJA KARYAWAN - Iba Gunawan; Muhamad Riza (Progress: Jurnal Pendidikan, Akuntansi dan Keuangan, 2019)
Indonesia Power UP Suralaya Cilegon as one of the State-Owned Enterprises currently employs as many as 733 people with various expertise and education levels.With the large number of employees/worker involved in the company PT. Indonesia Power UP Suralaya Cilegon, researchers are interested in reviewing or knowing whether there is a significant influence on the level of education on the work performance of employees in the company. The method used in this research is descriptive method with quantitative analysis. The sample in this study were 110 employees from 733 employees of PT Indonesia Power UpSuralayaCilegon. Data collection techniques used are questionnaire methods. The data analysis technique used is multiple linear regression analysis technique with the hypothesis test used is the t test and F test. Based on the results of the study it can be concluded that (1) The results of the calculation of the percentage of employee education level taken based on the respondent's overall answer of 80% which shows that most of the employees in the company have high school / vocational education. 2) With a significance of 5% it can be obtained the price of r table 1.661. It turns out that r count is greater than r table (0.276> 1.661), so the Hypothesis is rejected so that the Education Level does not have a significant effect on Employee Performance. Judging from the results of the output on the analysis of the calculation of the t test above, it can be concluded that the variable level of employee education does not affect employee performance. This is because the value of t count> t table (-2.240 <1.661) or significance <0.05 (0.029 <0.05) so the hypothesis is rejected.